The Impact of the Digital Economy on Sustainable Human Development in Iraq from 2004 to 2022 - nadia abdelqader (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The rapid expansion of digital technologies has transformed economic and social systems globally, with the digital economy seen as a driver of sustainable human development (SHD). Specific Background: Iraq, despite heavy investment in ICT infrastructure since 2003, has experienced stagnant Human Development Index (HDI) growth and a declining Human Capital Index (HCI), raising questions about the effectiveness of its digitalization. Knowledge Gap: While macroeconomic studies often explore technology–growth links, limited research examines how digital adoption affects human development in fragile, resource-based economies, particularly regarding adjustment lags and skill deficits. Aims: This study investigates the relationship between digital economy indicators (internet subscriptions, mobile usage, and e-government services) and SHD in Iraq from 2004–2022, using autoregressive distributed lag (ARDL) and error correction model (ECM) approaches. Results: Findings show that internet expansion and mobile penetration positively influence HDI, whereas weak human capital and institutional inefficiencies undermine digital dividends. Adjustment to equilibrium takes approximately 3.2 years, reflecting delayed impacts of digital shocks. Novelty: This research provides the first empirical analysis of Iraq’s digital economy–HDI nexus using high-frequency data, introducing the Digital Absorptive Capacity framework. Implications: Policymakers must shift from infrastructure-centric to human-centered strategies, emphasizing digital literacy, education reform, and institutional transparency to harness digitalization for inclusive development.Highlight : Internet and mobile penetration contribute positively to human development. Lack of digital skills limits the benefits of the digital economy. Digital education reforms and governance integrity are key for sustainability. Keywords : Digital Economy, Sustainable Human Development, ARDL Model, Error Correction Mechanism, Human Capital Index